Authority in statebuilding as communicative practice. The Joint Working Group on the Constitutional Framework in Kosovo. Issue 3 (16th April 2017) - Distler, Werner
ABSTRACT: Post-war constitution-making touches the future identity of the concerned society. In externally led democratization, it can turn into a challenging negotiation process between international and so-called local actors. But who can claim the authority to define and interpret identity and fundamental norms of society, and on what grounds? Based on an analysis of the "Joint Working Group on the Constitutional Framework" held in spring 2001 in Kosovo, the article argues that external actors have a structural disadvantage in the authoritative communication with local actors, even if equipped with a strong international mandate. While external actors can set the opportunity structures to negotiate constitutional politics, local actors will use every chance to publically claim authority on their behalf in the process. Guided by the theoretical framework of interpretative authority ( Deutungsmacht ), the article concludes that we have to understand authority in statebuilding primarily, not as an attribute of actors, but as an outcome of communicative practices.